PERAN UNITED NATIONS WORLD FOOD PROGRAMME (UNWFP) MENANGGULANGI KRISIS PANGAN ZIMBABWE TAHUN 2019-2023 - Istiqomah, Fitri Al (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2025)
ABSTRACT Zimbabwe has once again faced a severe food crisis due to Cyclone Idai and the Covid-19 pandemic, which posed a serious threat to food security despite previous improvements in 2017. In response, Zimbabwe received support from UNWFP and managed to exit the list of the ten worst food crisis countries. This research aims to explain the role of the UNWFP in addressing the food crisis in Zimbabwe from 2019 to 2023, using qualitative methods and desk research, and is analysed through role of international organizational theory. The findings show that the UNWFP served as an instrument, but its roles as an arena and actor remained limited due to implementation being dominated by Zimbabwean government authorities. This study contributes to the literature gap concerning the limited roles of international organisations due to domestic factors. Practically, it highlights the importance of synergy between international organisations and local governments, as well as the need for transparency and accountability in aid management to enhance the effectiveness of food security programmes.